2013
DOI: 10.1186/1475-2891-12-160
|View full text |Cite
|
Sign up to set email alerts
|

Improving lactose digestion and symptoms of lactose intolerance with a novel galacto-oligosaccharide (RP-G28): a randomized, double-blind clinical trial

Abstract: BackgroundLactose intolerance (LI) is a common medical problem with limited treatment options. The primary symptoms are abdominal pain, diarrhea, bloating, flatulence, and cramping. Limiting dairy foods to reduce symptoms contributes to low calcium intake and the risk for chronic disease. Adaptation of the colon bacteria to effectively metabolize lactose is a novel and potentially useful approach to improve lactose digestion and tolerance. RP-G28 is novel galacto-oligosaccharide (GOS) being investigated to imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
91
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 21 publications
0
91
0
3
Order By: Relevance
“…The clinical trial included subjects who consumed GOS but refrained from consuming dairy for 36 d, then stopped GOS consumption and reintroduced dairy into their diets for 30 additional days, until day 66. The changes in microbiome composition reported here included increases in lactose-fermenting Bifidobacterium, Lactobacillus, and Faecalibacterium, and those changes correlated with an improvement of symptoms for lactose-intolerant subjects who were participating in the study (4). In this aligned clinical study, 50% of the subjects with abdominal pain at baseline reported no abdominal pain at the end of treatment with GOS (at day 36), and at 30 d posttreatment (at day 66) (P = 0.0190).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The clinical trial included subjects who consumed GOS but refrained from consuming dairy for 36 d, then stopped GOS consumption and reintroduced dairy into their diets for 30 additional days, until day 66. The changes in microbiome composition reported here included increases in lactose-fermenting Bifidobacterium, Lactobacillus, and Faecalibacterium, and those changes correlated with an improvement of symptoms for lactose-intolerant subjects who were participating in the study (4). In this aligned clinical study, 50% of the subjects with abdominal pain at baseline reported no abdominal pain at the end of treatment with GOS (at day 36), and at 30 d posttreatment (at day 66) (P = 0.0190).…”
Section: Discussionmentioning
confidence: 99%
“…Eligible subjects were required to demonstrate a minimum symptom score and a positive HBT to be eligible for randomization. Exclusion criteria included diabetes mellitus, GI motility disorders, irritable bowel syndrome, inflammatory bowel diseases, celiac disease, and surgery that altered the normal function of the GI tract (4). During the clinical trial, participants avoided lactose in their diets and received escalating doses of high-purity (>95%) GOS or placebo (Sweetose) in 5-d increments according to a fixed schedule from 1.5 g/d to 15 g/d.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In clinic, prebiotics have also been trialed for their benefits in various diseases [127][128][129][130][131]. Oligofructose (OFS), an inulin-type fructans, were added to diet for patients with NASH in a pilot randomized double-blind study [118].…”
Section: Gut Microbiota-targeted Therapy With Prebioticmentioning
confidence: 99%